Optimal Design of Cyclic Prefix in MIMO-OFDM System Over Nakagami-m Fading Channel - Ho, Van-Cuu; Le, Hoang-Hiep; Nguyen, Thu-Hang Thi (AETA 2016: Recent Advances in Electrical Engineering and Related Sciences, 2016)
This study attempts to find out the optimal number of cyclic prefix (CP) for a 2 × 2 multiple-input multiple-output – orthogonal frequency division multiplexing (MIMO-OFDM) system over Nakagami-m fading channel. Channel simulation and evaluation is for such a system in which data are sent from two transmit antennas to two receive antennas. In this research, the authors have used binary phase shift keying (BPSK) technique to modulate data stream. They have also presented and compared transmission performance of the system in several different environmental propagations such as Nakagami-m, Rician, Rayleigh multipath fading channels, and additive white Gaussian noise (AWGN) channel. Specifically, in Nakagami-m fading channel case, this research minimized number of CP subject to transmission performance is still acceptable. MATLAB tool and Monte Carlo simulation method is used to estimate for the results in this paper.